2005
DOI: 10.1212/01.wnl.0000176069.64200.28
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset episodic ataxia type 2 due to an in-frame insertion in CACNA1A

Abstract: Episodic ataxia type 2 (EA2) is caused by calcium channel (CACNA1A) mutations and typically begins before age 20 years. The molecular basis of late-onset EA2 is unclear. The authors describe a case of late-onset EA2 associated with the first multiple-base pair insertion in CACNA1A. Molecular expression revealed evidence of impaired calcium channel function, suggesting that genetically induced reduction in calcium channel function may associate with cases of late-onset EA2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 10 publications
0
42
0
1
Order By: Relevance
“…In fact, a dominant negative effect of several missense and truncation mutants was found when the EA2 mutations were inserted in certain Ca V 2.1 isoforms, including a human Ca V 2.1 with a long C terminus [52,54,93], but not when they were inserted in a human Ca V 2.1 with a short C terminus [35,42,43,52,140]. Moreover, oocytes expressing short human Ca V 2.1 channels carrying four different EA2 mutations, including two mutations that in mammalian cells led to complete loss of function of the channel [139,140], displayed a measurable (although strongly reduced) Ca 2+ current [42,43,140]. Differences in the ER retention and cellular degradative capacities between oocytes and mammalian cells likely explain the different loss-of-function and dominant negative effects of EA2 mutants in the two expression systems.…”
Section: Functional Consequences Of Ea2 Mutations On Recombinant Humamentioning
confidence: 99%
“…In fact, a dominant negative effect of several missense and truncation mutants was found when the EA2 mutations were inserted in certain Ca V 2.1 isoforms, including a human Ca V 2.1 with a long C terminus [52,54,93], but not when they were inserted in a human Ca V 2.1 with a short C terminus [35,42,43,52,140]. Moreover, oocytes expressing short human Ca V 2.1 channels carrying four different EA2 mutations, including two mutations that in mammalian cells led to complete loss of function of the channel [139,140], displayed a measurable (although strongly reduced) Ca 2+ current [42,43,140]. Differences in the ER retention and cellular degradative capacities between oocytes and mammalian cells likely explain the different loss-of-function and dominant negative effects of EA2 mutants in the two expression systems.…”
Section: Functional Consequences Of Ea2 Mutations On Recombinant Humamentioning
confidence: 99%
“…7,9 -11 Such late onset may be related to certain mutations, such as, for example, multiple-base pair insertions in CACNA1A. 12 Clinically, EA 2 is characterized by recurrent attacks of ataxia lasting for several hours to days, which are provoked by physical exertion, emotional stress, or alcohol. 9,13 Several patients also have mild myasthenic symptoms (due to impaired neuromuscular transmission; see below).…”
Section: Clinical Features Of Episodic Ataxia Typementioning
confidence: 99%
“…The Ca v 2.1 calcium channel subtype regulates neurotransmission throughout the nervous system, but is predominantly expressed within cerebellar Purkinje cells (Usowicz et al, 1992;Stea et al, 1994;Westenbroek et al, 1995). Not surprisingly, cerebellar dysfunction is the primary feature of EA2 attacks, as patients experience bouts of symptoms such as ataxia, migraine and vertigo, in response to Functional expression studies involving EA2 mutations have firmly established that non-or hypo-conductive α 1 2.1 subunits cause the disorder (Guida et al, 2001;Jen et al, 2001;Jouvenceau et al, 2001;Wappl et al, 2002;Imbrici et al, 2004;Spacey et al, 2004;Imbrici et al, 2005;Wan et al, 2005b;Jeng et al, 2006), which is largely but not exclusively associated with expression of α 1 2.1 truncation mutants (Ophoff et al, 1996;Yue et al, 1998;Battistini et al, 1999;Denier et al, 1999;Jen et al, 1999;Denier et al, 2001;van den Maagdenberg et al, 2002;Wappl et al, 2002;Subramony et al, 2003;Jen et al, 2004;Mantuano et al, 2004;Eunson et al, 2005;Spacey et al, 2005;Wan et al, 2005a;Wan et al, 2005b;Scoggan et al, 2006). However, the molecular mechanisms by which nonfunctional α 1 2.1 pores generate disease in EA2 are still debated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms by which nonfunctional α 1 2.1 pores generate disease in EA2 are still debated. Although some studies have suggested that the loss of channel function in EA2 simply induces a haplo-insufficiency of Ca v 2.1 currents (Wappl et al, 2002;Imbrici et al, 2004;Imbrici et al, 2005), substantial evidence argues that non-conductive α 1 2.1 mutants in EA2 actually suppress the functional contributions of Ca v 2.1 channels composed of wild-type subunits through a dominantnegative mechanism (Jouvenceau et al, 2001;Raghib et al, 2001;Arikkath et al, 2002;Page et al, 2004;Jeng et al, 2006). Studies have suggested that impaired translation or stability of wild-type α 1 2.1 subunits contributes to EA2 pathogenesis (Raghib et al, 2001;Page et al, 2004), while other evidence implicates the interactions between non-conductive α 1 2.1 mutants and auxiliary β subunits in the dominant-negative suppression of wild-type α 1 2.1 subunit function (Arikkath et al, 2002;Jeng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%